IMPLEMENTASI LANDING PAGE INTERAKTIF DAN MEDIA SOSIAL UNTUK MENINGKATKAN LOYALITAS PELANGGAN UMKM MADU HERBAL - Sanita Dhakirah; Farida Akbarina; Win Narasuci; Maskur Maskur; Prima Beauty Kartikasari; Lilies Nur Aini (P3M Politeknik Negeri Malang, 2025)
This community service program aims to optimize Customer Relationship Management (CRM) through the development of an interactive landing page and structured social media content strategy for UMKM Hexa Anugerah Bersinar, a producer of premium herbal honey in Malang. The problem addressed includes limited customer interaction, lack of digital marketing utilization, and absence of structured customer data management. The method applied consisted of training, mentoring, and implementation of CRM systems, interactive landing page design, and social media content development using storytelling, education, and testimonials. The results show that the new Nutri Bunga landing page (https://nutribunga.netlify.app) successfully functions as a customer engagement entry point, while the Instagram account (@nutribunga_) rebranding increases brand visibility with structured educational content. Early monitoring indicates an increase in customer engagement and higher product conversion rates. This initiative contributes to strengthening MSME’s competitiveness by integrating digital-based customer engagement strategies.